Attitudes and acceptance of patients undergoing visceral surgery towards an open access electronic medical record – a Swiss-German single-centre study (Swiss Medical Weekly, 2020)
INTRODUCTION With the digitalisation of patient medical records, providing patients with free access to their electronic medical record (EMR) has become an important topic of debate in many countries. Recent studies show that the quality of treatment in healthcare may be improved by encouraging patients to take an active part in their care. Providing patients with access to their EMR may also improve the patient-doctor relationship, adherence to treatment and patient satisfaction. In June 2015, the Swiss government passed a law to set the framework for a nationally coordinated EMR system. A major stipulation to this legislation is that patients and doctors must consent to having an open access EMR (oEMR). The aim of this study was to assess patients’ attitudes towards an oEMR. METHODS Consecutive patients attending the outpatient clinic of our department within two months were included in this study. Patients were asked to complete a questionnaire consisting of 43 items, including amongst others disease characteristics, their expectations regarding an oEMR and its implementation. This study was approved by the ethics committee of the Canton Zurich (BASEC-Nr. Req-2016-00383). RESULTS 149 patients were included with a mean age of 52 (standard deviation 17) years. 42% suffered from abdominal diseases (benign or malignant), 26% from hernias, and 17% from anorectal disorders. 76% of the responding patients fully supported an oEMR. Among all items, a higher educational degree (odds ratio [OR] 55, 95% confidence interval [CI] 39–70), patients with general or half-private insurance (OR 10, 95% CI 0.99–100) and patients with suspected cancer (OR 6, 95% CI 0.93–42) were independent predictors for a positive attitude regarding an oEMR on multivariate analysis. CONCLUSION To our knowledge, this is the first study conducted in a hospital in the German-speaking part of Switzerland evaluating patients’ opinions regarding an oEMR. Overall a large majority of the patients support an oEMR. Patients with cancer, a higher educational degree and general or half-private insured patients were more likely to support an oEMR. An important next step would be to conduct studies investigating opinions of medical professionals during the implementation of an oEMR.